KUALITAS FISIK DAGING DARI PASAR TRADISIONAL DI BANDAR LAMPUNG - Alda Nasrul Haq; Dian Septinova; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The increasing amount of populations makes the beef demand increased. This case should be followed by the quality of beef sold. The beef quality sold in traditional market can be identified by conducting the physical test of beef, that is finding out the pH, water holding capacity, and cooking losses. This research was aimed to find out the beef quality through physical testing (pH, water holding capacity, and cooking losses) at traditional markets in Bandar Lampung city. The method used in this research was survey. Data collecting techniques were purposive sampling and questionnaire based on the requirements specified such as: the number of beef sales >25 kg/day, one’s own/ permanent work, and at least 2 years selling, The beef samples taken were about 300 grams. Questionnaire was used to find out the origin of beef, cutting time, market condition, sales area, and equipments used. The result of beef’s physical quality from traditional market in Bandar Lampung city showed normal value. The estimation value of pH was 5,47-6,99, water holding capacity was 44,31-77,6, and cooking losses was 4,64-27,91. Overall, the quality of beef sold at traditional market in Bandar Lampung city was normal. (Keywords: Physical quality, Beef)